Potential Solutions - Keys, Joe, 1995- (2021)
Potential Solutions examines my art practice in the context of contemporary art in Iceland, looking firstly at my perspective on gathering material to make art with, then broadening this inquiry to include artists that I relate to. I focused on material that I find in everyday circumstances, often single-use plastics and stationary and consider how and why I work with these things. After this, I discuss repetition and its relationship to artists as a method of honing a craft or as a concept in itself, predominantly through the practice of installing exhibitions with multiple frames filling gallery walls. Later in the text, I looked at containers and how they complicate my interpretation of objects and function, as they exist as accessories to hold objects. The chapter looks at my developing intrigue from what the container holds, to then my sole interest in the container itself. I have researched many artists that have influenced me, through critical texts in exhibition catalogues, monographs, and online journals. A significant amount of the thesis is informed by the philosophy of Jean Baudrillard’s The System of Objects, which gave me a context to discuss the logic and utility, or lack of, in the objects I have worked with. As well as this I discuss Duchamp’s Readymades and the Fluxus movement, two historical moments that revere the everyday. The works of mine I discuss put forward an idealistic way of organising, a suggestion of how objects should exist, with an awareness that these suggestions are not pressing or necessary. It is hard to imagine, as I contemplate a career of art-making, that I could be tackling the same drawing or sculpture for 30 years, yet I empathise with that drive of many artists to understand one certain subject.